Prevalence of Triple Burden of Malnutrition (Stunting, Obesity, Anaemia) among Toddlers in Jakarta Slums - Wiji, Wijianto; Mareyke Yolanda Lusia Sepang; Kandace Sianipar (CV. Get Press Indonesia, 2025)
The triple burden of malnutrition (stunting, obesity, and anaemia) is a serious problem experienced by toddlers in Jakarta's slums, with a prevalence reaching more than one-third of the population. The objective of this study is to ascertain the prevalence and coexistence patterns of these events in toddlers residing in the Jakarta area. The data presented herein were collected through the utilisation of structured interviews, employing a standardized questionnaire, with mothers/guardians of toddlers. The collected data were analysed univariately to determine the frequency distribution of respondent characteristics and nutritional status, followed by bivariate analysis to test the relationship between independent variables (socioeconomic factors, consumption patterns, access to health services) with nutritional status using the chi-square test, and multivariate with multiple logistic regression. The prevalence of stunting was 36.2%, and obesity was 16.2%. The coexistence of two or three forms (double/triple burden) was found in nearly 36.4% of children. Maternal education, family income below the minimum wage (UMP), imbalanced dietary patterns, and irregular access to integrated health service posts (Posyandu) were statistically significantly associated with the risk of triple burden. The findings of this study provide a robust and valid depiction of the concurrent burden of nutritional problems in children residing in a deprived urban area. The study also serves as a foundation for the formulation of integrated and evidence-based nutrition intervention programmes.